Peran Dana Sosial Islam Dalam Perencanaan Keuangan Keluarga - Muhammad Ghufron Afandi; Luluk Maulidia; Rini Puji Astuti; Ristian Sinta (CV. KAMPUSA AKADEMIK PUBLISING, 2025)
Abstrak. The important role of Islamic social funds, namely waqf, zakat, and Islamic social finance in supporting family financial planning. Islamic social funds have a plan to improve the welfare and economic maturity of families through proper distribution and management based on sharia principles. This study uses a qualitative descriptive method, namely through data-based research collected through interviews, observations, and documentation at Islamic social fund management institutions. The results of this study indicate that optimizing Islamic social funds can be an important instrument in family financial planning, especially in meeting basic needs and education. This concept provides a more organized and participatory social fund management strategy to empower families as a whole.